2019
DOI: 10.1080/23746149.2019.1634487
|View full text |Cite
|
Sign up to set email alerts
|

Reactive force field simulations of silicon clusters

Abstract: The fast and continuous growth of multidisciplinary approaches, consisting of the combination of various experimental techniques and computational methods tuned on purpose to depict and predict material properties and performance, is motivated by the need to design new superior devices for effective applications in a great variety of industrial sectors. This strategy not only produces excellent results but is also fundamental to drive the research towards innovative and cost-effective production systems. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Despite the fact that the vacancy in crystalline silicon has been studied for a long time using various methods, a relatively little attention is paid to the presence and stability of the vacancy in silicon nanoparticles. Although a number of researches on vacancy in nanosilicon have been provided [11][12][13][14], detailed studies of its geometric configuration and positions of electronic levels were done only in several of them [13,15]. Thus, size effects on the vacancy formation energy and entropy were considered in [13] and it was found that the size reduction makes the vacancy much easier to form; then, the vacancy concentration increases with reducing size and increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the vacancy in crystalline silicon has been studied for a long time using various methods, a relatively little attention is paid to the presence and stability of the vacancy in silicon nanoparticles. Although a number of researches on vacancy in nanosilicon have been provided [11][12][13][14], detailed studies of its geometric configuration and positions of electronic levels were done only in several of them [13,15]. Thus, size effects on the vacancy formation energy and entropy were considered in [13] and it was found that the size reduction makes the vacancy much easier to form; then, the vacancy concentration increases with reducing size and increasing temperature.…”
Section: Introductionmentioning
confidence: 99%